Confronting the neo-liberal brute: Reflections of a higher education middle-level manager - Maistry, Suriamurthee Moonsamy (South African Journal of Higher Education, 2016)
The higher education scenario in South Africa is fraught with tensions and contradictions. Publicly funded Higher Education Institutions (HEIs) face a particular dilemma. They are expected to fulfill a social mandate which requires a considered response to the needs of the communities in which they are located while simultaneously aspiring for national and global competitiveness. While it may be argued that these mandates are not in tension with one another, in this paper I argue that the reckless appropriation of neo-liberal, western performance-driven models grounded in economic rationalism translates into a form of subtle and sometimes overt ‘violence’ against and humiliation of marginalized individuals and groups within the university community. I engage the tenets of self-study methodology to reflect on my practice as a middle-level manager (head of school) at a recently merged HEI in KwaZulu-Natal. In particular, I reflect on my complicity in and my attempts to temper the effects of alienating, market-driven university discourse and culture. Drawing on Nussbaum’s (2003; 2011, 2010) and Sen’s inspirational work on human capabilities (2009; 2005, 1999) and Arendt’s insights on what it takes to think in ‘dark times’(2006, 1998), I argue that a focus on capabilities rather than achievements is a useful way of engaging the development of higher education personnel as it signals the notions of care and respect as endearing human values that higher education institutions should not neglect in their quest for market share in a hostile neo-liberal environment.